Rates of and Reasons for Revisits after Deliveries with and without Severe Maternal Morbidity. (20th August 2020) - Reid, L.; Fingar, K.; Barrett, M.; McDermott, K.; Ngo‐Metzger, Q.; Owens, P.
Abstract : Understanding the frequency of and reasons for postpartum revisits, which occur more often for women with delivery complications than for those without, can help identify risk and inform discharge care. The objective of this study was to examine the rate of and reasons for inpatient and emergency department (ED) revisits 7 days and 42 days following deliveries with and without severe maternal morbidity (SMM). Retrospective conveys the intended meaning. cohort study using data from the Agency for Healthcare Research and Quality's 2016‐2017 Healthcare Cost and Utilization Project State Inpatient Databases and State Emergency Department Databases from 14 states with de‐identified patient linkage numbers and adequate race/ethnicity coding (AR, FL, GA, IA, MD, MS, MO, NV, OR, SC, SD, TN, VT, and WI). The analysis consisted of delivery hospitalizations and postpartum inpatient and ED revisits for women aged 12‐55 years. SMM conditions at delivery were grouped into eight types: severe cardiac conditions, sickle cell disease with crisis, severe hypertensive disorders, severe respiratory conditions, sepsis, severe hemorrhage, other severe obstetric conditions, and other severe medical conditions. Outcomes included 7‐day and 42‐day inpatient and ED age‐adjusted revisit rates and the reason for the revisit. A total of 9164 index deliveries with an SMM condition and 1 406 582 deliveries without an SMM condition at delivery were included. Of those deliveries with an SMM condition, 35.0% were for black women and 23.1% were for women aged 35 years and older compared with 22.4% and 15.2% of deliveries without an SMM condition, respectively. Overall, 73.2 per 1000 deliveries with an SMM condition had an inpatient or ED revisit within 7 days and one in five women returned within 42 days postpartum (207.0 revisits per 1000 deliveries). These rates were more than twice as high as those for deliveries without an SMM condition (32.1 and 87.7 per 1000, respectively). Among women with only one SMM type at delivery, the 42‐day revisit rate for inpatient or ED care was as high as 445.5 per 1000 deliveries with sickle cell disease with crisis, followed by 250.9 per 1000 deliveries with severe cardiac conditions. An additional 2400 women without an SMM condition diagnosed at delivery had an inpatient readmission within 7 days for an SMM‐related condition. Women with the highest postpartum revisit rates included those with a diagnosis of SMM at delivery overall and specifically those with sickle cell disease with crisis and severe cardiac conditions. A number of women with SMM conditions were diagnosed at a postpartum readmission and not at the delivery. Examining revisits during the postpartum period is an important consideration when studying SMM. This study can help identify women at high risk of postpartum revisits. The data can be used to inform the scheduling and content of coordinated discharge care, assist with resource allocation, and identify research priorities for maternal care. Future research is needed to examine the contributions of clinical factors at delivery, expected payer, and hospital and community characteristics in explaining disparities in the risk of postpartum readmission. Agency for Healthcare Research and Quality.